2022
DOI: 10.2478/aoas-2021-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded dietary inclusion levels of hybrid rye grain on productive performance, the cost-effectiveness of nutrition and egg quality in laying hens

Abstract: The study was designed to investigate productivity parameters, egg quality and the cost effectiveness of feeding laying hens with diets where ground wheat was replaced with varying levels of whole hybrid rye grain cv. Brasetto. A total of 396 Hy-Line Brown hens at 34 weeks of age were allocated to three treatment groups with 66 replicates (cages) of two hens each, and were fed isocaloric and isonitrogenous pelleted diets for 12 weeks. The diet for control group hens (R0) did not contain rye grain. In diets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…However, xylanase positively influenced eggshell thickness, but only in eggs from hens fed the ryewheat-corn diet, while the effect on eggshell density was only observed in eggs from layers fed the wheat-corn diet. These results are generally in agreement with previous studies, such as that by Mikulski et al [35] which also showed that when diets containing hybrid rye (up to 20%) are supplemented with NSP-degrading enzymes, no significant effect on eggshell thickness is observed. Our results agree with other previous studies that have shown no effect of xylanase on eggshell weight or thickness in eggs from hens fed a wheat-based diet alone [36,37] or diets with 10% rye inclusion [38].…”
Section: Discussionsupporting
confidence: 93%
“…However, xylanase positively influenced eggshell thickness, but only in eggs from hens fed the ryewheat-corn diet, while the effect on eggshell density was only observed in eggs from layers fed the wheat-corn diet. These results are generally in agreement with previous studies, such as that by Mikulski et al [35] which also showed that when diets containing hybrid rye (up to 20%) are supplemented with NSP-degrading enzymes, no significant effect on eggshell thickness is observed. Our results agree with other previous studies that have shown no effect of xylanase on eggshell weight or thickness in eggs from hens fed a wheat-based diet alone [36,37] or diets with 10% rye inclusion [38].…”
Section: Discussionsupporting
confidence: 93%
“…Egg chemical composition can be influenced by factors such as age, the genes of the hens, or the housing system [8,9]. The specific composition of their feed also affects egg composition [10][11][12][13]. Specifically, the FA profile can be modified.…”
Section: Introductionmentioning
confidence: 99%